Corticospinal excitability following short-term motor imagery training of a strength task - Leung, M. C. M.; Spittle, M.; Kidgell, D. J. (Journal of Imagery Research in Sport and Physical Activity, 2013)
Motor imagery and actual movement engage similar neural structures, however, whether they produce similar training-related corticospinal adaptations has yet to be established. The aim of this study was to compare changes in strength and corticospinal excitability following short-term motor imagery strength training and short-term strength training. Transcranial magnetic stimulation (TMS) was applied over the contralateral motor cortex (M1) to elicit motor-evoked potentials in the dominant biceps brachii muscle prior to and following 3-week strength training using actual bicep curls or motor imagery of bicep curls. The strength training (n = 6) and motor imagery (n = 6) groups underwent three supervised training sessions per week for 3 weeks. Participants completed four sets of six to eight repetitions (actual or imagined) at a training load of 80% of their one-repetition maximum. The control group (n = 6) were required to maintain their current level of physical activity. Both training groups exhibited large performance gains in strength (p < 0.001; strength training 39% improvement, imagery 16% improvement), which were significantly different between groups (p = 0.027). TMS revealed that the performance improvements observed in both imagery and strength training were accompanied by increases in corticospinal excitability (p < 0.001), however, these differences were not significantly different between groups (p = 0.920). Our findings suggest that both strength training and motor imagery training utilised similar neural substrates within the primary M1, however, strength training resulted in greater gains in strength than motor imagery strength training. This difference in strength increases may be attributed to adaptations during strength training that are not confined to the primary M1. These findings have theoretical implications for functional equivalent views of motor imagery as well as important therapeutic implications.